2002
DOI: 10.1023/a:1016518920693
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Rats treated with DOCA salts and subjected to abdominal aortic stenosis display left ventricle hypertrophy associated with a decrease in cardiac I(to) current density and prolongation of the action potential duration. We investigated the molecular basis of these electrophysiological defects by analyzing the amount of mRNA corresponding to the genes encoding the a subunits of the left ventricle K+ channel at the steady state. The mRNAs corresponding to the a subunits of the K+ channel (Kv1.2, Kv1.4, Kv1.5, Kv2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“… 8 , 9 , 30 Accordingly, we demonstrated that the I to current density was downregulated in response to pressure overload, which could be prevented by candesartan cilexetil treatment. However, the I ss and I K1 densities as well as the corresponding Kv2.1 and Kir2.1 protein levels were not changed, as reported previously, 34 , 35 excluding their involvement in APD prolongation. Peak I Na is mainly responsible for the upstroke of cardiac action potential.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 8 , 9 , 30 Accordingly, we demonstrated that the I to current density was downregulated in response to pressure overload, which could be prevented by candesartan cilexetil treatment. However, the I ss and I K1 densities as well as the corresponding Kv2.1 and Kir2.1 protein levels were not changed, as reported previously, 34 , 35 excluding their involvement in APD prolongation. Peak I Na is mainly responsible for the upstroke of cardiac action potential.…”
Section: Discussionsupporting
confidence: 86%
“…In rat LV hypertrophy, Kv4.2 and Kv4.3 mRNA are downregulated with no accompanying change in Kv1.4 mRNA. 34 Our results further confirmed the downregulation of both Kv4.2 and Kv4.3 protein and mRNA levels, with no changes in Kv1.4 or KChIP2 protein in the hypertrophied left ventricle. Chronic candesartan cilexetil treatment preserved the I to density accompanied by normal recovery kinetics in banded rat myocytes, perhaps mainly by restoring the Kv4.2 and Kv4.3 channel expression.…”
Section: Discussionsupporting
confidence: 84%
“…The Ca v 3.1, Ca v 3.2, cyclophylin primers, and quantitative RT–PCR procedures have been described elsewhere. 5,15 Briefly, quantitative RT–PCR was performed with a normalized RNA aliquot (1 µg) and a known amount of cRNA internal control (2.5 × 10 6 molecules). The internal control differed from the target counterpart by only one restriction site.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the relation between corticosteroids and potassium channels, deoxycorticosterone acetate salt treatment alters the amount of K v transcripts, suggesting that mineralocorticoids may be involved in K v gene expression [15]. Chronic dexamethasone treatment also decreases the transient outward current ( I to ) density [16], which would be expected to enhance the transmural dispersion of repolarization. In Andersen–Tawil syndrome, a rare disorder of periodic paralysis caused by mutations in the KCNJ2 gene, which encodes the inward rectifier potassium channel Kir 2.1, stress or corticosteroids exacerbate the symptoms [17, 18].…”
Section: Discussionmentioning
confidence: 99%